“Fundus animae” – Herder’s Concept of the Unconscious Ground of Human Subjectivity - Michalski, Rafał Andrzej (Studia Warmińskie, 2021)
The article discusses the concept of the ground of the soul (fundus animae), which is a very important element of Herder’s project of philosophical anthropology, and at the same time a necessary starting point for a proper understanding of most of his considerations in the field of the theory of knowledge, aesthetics and philosophy of language. The unconscious ground of the soul is the source of human psychophysical unity. Hidden in the „abyss of the soul”, synesthetic images, saturated with effects, constitute the foundation of cognitive processes and the semantic core of later concepts. The first section of the article discusses the category of vital force, which is the main metaphysical assumption of Herder’s theory. The second part contains a reconstruction of the early concept of fundus animae, while the third part analyzes its revised version, in which the philosopher refers to the notion of sensory attention (Besonnenheit) and to the findings of the 18th century physiology.